Metode Pembelajaran Kitab Fathul Mu’in di Pondok Pesantren Asy-Syarif Kecamatan Tilatang Kamang Kab. Agam - Zulpahri Hasibuan; Arman Husni (Lembaga Yasin AlSys, 2026)
The learning of kitab kuning is a distinctive feature of pesantren education that plays an important role in shaping students’ scholarly competence and understanding of Islamic jurisprudence. Although methods for learning kitab kuning have been widely studied, research that specifically discusses the learning of Fathul Mu’in and the obstacles to its implementation at Pondok Pesantren Asy-Syarif, Tilatang Kamang Subdistrict, Agam Regency, remains limited. This study aims to describe the learning methods of Fathul Mu’in and to identify the obstacles encountered in their implementation. This study employed a qualitative approach with a case study design, involving the head of the Islamic boarding school, the ustaz teaching Fathul Mu’in, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings show that the learning of Fathul Mu’in is implemented through the sorogan, bandongan, and halaqah methods, which are applied integratively according to the characteristics of the material and the students’ abilities. The main obstacles identified include limited mastery of nahwu and sharaf, inadequate mastery of Arabic vocabulary, low participation among some students, limited learning time, and students’ fatigue due to the density of learning activities. The conclusion of this study affirms that the effectiveness of learning Fathul Mu’in strongly depends on the application of varied, contextual methods that are aligned with students’ abilities. The implications of this study provide a theoretical contribution to the development of studies on kitab kuning learning in pesantren, as well as a practical reference for pesantren administrators and ustaz in designing Islamic jurisprudence learning strategies that are more adaptive, participatory, and oriented toward strengthening students’ scholarly competence.